It's Got the Look: The Effect of Friendly and Aggressive “Facial” Expressions on Product Liking and Sales - Landwehr, Jan R.; McGill, Ann L.; Herrmann, Andreas (Journal of Marketing, 2011)
When designing their products, companies try to employ shapes that are both emotionally appealing and compatible with the brand's image. One way to accomplish these aims is to anthropomorphize a product's appearance. The current research investigates how people decode emotional “facial” expressions from product shapes and how this affects liking of the design, using three studies in the domain of cars and one in the domain of cellular phones. In accordance with theories on the perception of human faces, the first study shows that perception of friendliness is limited to the grille (mouth), while aggressiveness can be communicated with both grille and headlights (eyes). The next study examines the best-liked combination of these two emotional expressions and finds that consumers prefer the combination of an upturned (friendly) grille with slanted (aggressive) headlights. The authors further explain this finding on a process level by showing that this combination triggers a positive affective state of both high pleasure and arousal. The third study validates the results with automobile sales data, and a fourth study extends the findings to another product category.